Exploring Physics Concepts in the Moke Distillation: An Ethnoscience Study of the JA Mokeasa Village - Alfred Aristo Guru Gesi; Pujianto; Eduardus Beo Seso Delvion (Universitas Nurul Huda, 2026)
This study aims to identify physics concepts in the moke refining process practiced by the community of Ja Mokeasa Village, Ende Regency, East Nusa Tenggara. Moke is a traditional beverage made from enau tree sap and holds important social and cultural value. This research employed a qualitative descriptive ethnoscience approach. Data were collected through two direct observations of the distillation process and in-depth interviews with two moke artisans, each lasting approximately 45–60 minutes. Data credibility was ensured through source and method triangulation by comparing observations, interviews, and documentation. Data analysis used the Miles and Huberman interactive model, including data collection, reduction, presentation, interpretation, and conclusion drawing. The findings reveal several physics concepts in the distillation process, such as temperature and heat, changes in states of matter, heat transfer mechanisms, and pressure relationships. The moke distillation process has the potential to be used as a contextual learning resource in science or physics education by integrating local wisdom with scientific concepts.